Cryopreserved platelets demonstrate reduced activation responses and impaired signaling after agonist stimulation. Issue 12 (14th September 2017) - Waters, Lauren; Padula, Matthew P.; Marks, Denese C.; Johnson, Lacey
Abstract : BACKGROUND: Room temperature–stored (20‐24°C) platelets (PLTs) have a shelf life of 5 days, making it logistically challenging to supply remote medical centers with PLT products. Cryopreservation of PLTs in dimethyl sulfoxide (DMSO) and storage at –80°C enables an extended shelf life up to 2 years. Although cryopreserved PLTs have been widely characterized under resting conditions, their ability to undergo agonist‐induced activation is yet to be fully explored. STUDY DESIGN AND METHODS: Buffy coat PLTs were cryopreserved at –80°C with 5% to 6% DMSO and sampled before freezing and after thawing. PLTs were analyzed under resting conditions and after agonist stimulation with adenosine diphosphate, collagen, or thrombin receptor–activating peptide‐6. The expression of activation markers, microparticle formation, and calcium mobilization were analyzed by flow cytometry. Soluble PLT proteins present in the PLT supernatant were examined by enzyme‐linked immunosorbent assay. Protein phosphorylation was investigated with Western blotting. RESULTS: After cryopreservation, PLTs displayed increased surface activation markers and higher basal calcium levels. Cryopreserved PLTs demonstrated diminished aggregation responses. Additionally, cryopreserved PLTs showed a limited ability to become activated (as measured by CD62P and phosphatidylserine exposure and cytokine release) after agonist stimulation. A reduction in the abundance and phosphorylation of key signaling proteins (Akt, Src, Lyn, ERK, and p38) was seen in cryopreserved PLTs. CONCLUSIONS: Cryopreservation of PLTs induces dramatic changes to the basal PLT phenotype and renders them largely nonresponsive to agonist stimulation, likely due to the alterations in signal transduction. Therefore, further efforts are required to understand how cryopreserved PLTs achieve their hemostatice ffect once transfused.